1978
DOI: 10.1029/jb083ib11p05473
|View full text |Cite
|
Sign up to set email alerts
|

On isostatic geoid anomalies

Abstract: In regions of slowly varying lateral density changes, the gravity and geoid anomalies may be expressed as power series expansions in topography. To a good approximation, geoid anomalies in isostatically compensated regions can be directly related to the local dipole moment of the density‐depth distribution. This relationship is used to obtain theoretical geoid anomalies for different models of isostatic compensation. The classical Pratt and Airy models give geoid height‐elevation relationships which differ in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
180
0
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(194 citation statements)
references
References 12 publications
12
180
0
2
Order By: Relevance
“…These are all relative geoid lows confirming the correlations found by Nakanishi and Anderson [1984]. Dense regions of the mantle that are in isostatic equilibrium also generate geoid lows [Haxby and Turcotte, 1978;Hager, 1983]. Dense regions in dynamic equilibrium generate geoid lows if the viscosity does not increase too rapidly with depth [Hager, 1984].…”
Section: Introductionsupporting
confidence: 71%
“…These are all relative geoid lows confirming the correlations found by Nakanishi and Anderson [1984]. Dense regions of the mantle that are in isostatic equilibrium also generate geoid lows [Haxby and Turcotte, 1978;Hager, 1983]. Dense regions in dynamic equilibrium generate geoid lows if the viscosity does not increase too rapidly with depth [Hager, 1984].…”
Section: Introductionsupporting
confidence: 71%
“…The models usually used in discussing the isostatic geoid (7)(8)(9)17) are obtained by assuming 1) that the half-space equation (3) is applicable, and 2) that only local density contrasts (the k -0 wavenumber) is important. This is equivalent to assuming a one-dimensional density model.…”
Section: Discussionmentioning
confidence: 99%
“…Oceanic heat flow can be explained by these models if hydrothermal activity at the ridge is taken into account (6); recently it has been demonstrated that the short wavelength change in geoid elevation over ridges predicted by these simple models is also readily observed (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The geoid data are known to relate linearly to the topography between wavelengths 400 km and 4000 km (Sandwell and Renkin, 1988), therefore, the GTR analysis for these wavelengths can be used to understand the mode of compensation of topographic features such as swells, plateaus and aseismic ridges (Haxby and Turcotte, 1978;Sandwell and McKenzie, 1989;Coblentz et al, 2011). In general, low GTR values (0-2 m/km) indicate shallow level of compensation, whereas, the intermediate GTR values (2-6 m/km) suggest that the compensation takes place at deeper level by lithosphere thinning (Crough, 1978).…”
Section: Geoid-topography Ratio (Gtr)mentioning
confidence: 99%